The Main Role of Digitalization For Hospitality Industry (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
Living in the digital age, the answer is probably all of it. From flights and hotels to browsing for fun things to making restaurant bookings, and using credit card rewards, there’s a whole ecosystem of apps and services that we can use to make each part of our trip quick and easy.